PENGARUH ENVIRONMENTAL PERFORMANCE, INTELLECTUAL CAPITAL DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Zhamaia, Della Zahra; Vivianti, Jenny (E-Jurnal Akuntansi TSM, 2024)
The purpose of this research was to dertermine the effect of environmental performance, intellectual capital, tax avoidance, managerial ownership, profitability, and leverage on firm value. In this research, firm value were measured by price to book value (PBV). The population in this study consists of companies in the consumer non-cyclicals, and basic materials sectors listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The sample used in this study were 39 companies, and the total data used was 117 data using a purposive sampling method. This research use multiple regression analysis method. The results of this study indicate that intellectual capital, tax avoidance, profitability and leverage have an influence on firm value, while environmental performance and managerial ownership have no effect on firm value.